1996
DOI: 10.1104/pp.111.3.797
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Levels of Free Linolenic and Linoleic Acids Increase in Tomato Leaves in Response to Wounding

Abstract: An intracellular signaling pathway for activating plant defense genes against attacking herbivores and pathogens is mediated by a lipid-based signal transduction cascade. I n this pathway, linolenic acid (18:3) is proposed to be liberated from cell membranes and is converted to cyclopentanones that are involved in transcriptional regulation of defense genes, analogously to prostaglandin synthesis and function in animals. Levels of 18:3 and linoleic acid in tomato (Lycopersicon esculentum) leaves increased with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(132 citation statements)
references
References 21 publications
5
123
1
3
Order By: Relevance
“…In accordance with this, immunocytochemical analysis revealed the specific occurrence of allene oxide cyclase, which converts allene oxide to OPDA, in ovules, the transmission tissue of the style and vascular bundles of receptacles, flower stalks, stems, petioles and roots (Hause et al 2000). This observation suggests that JA and related compounds may play some role in plant development, in addition to the response to external stimuli, such as wounding (Conconi et al 1996a;PenaCortes et al 1995), pathogen attack (Penninckx et al 1996) or UV-induced stress (Conconi et al 1996b). On the other hand, the KODA level is transiently increased at the very early stage of flower budding in D. caryophyllus, E. russelianum and P. nil.…”
supporting
confidence: 64%
“…In accordance with this, immunocytochemical analysis revealed the specific occurrence of allene oxide cyclase, which converts allene oxide to OPDA, in ovules, the transmission tissue of the style and vascular bundles of receptacles, flower stalks, stems, petioles and roots (Hause et al 2000). This observation suggests that JA and related compounds may play some role in plant development, in addition to the response to external stimuli, such as wounding (Conconi et al 1996a;PenaCortes et al 1995), pathogen attack (Penninckx et al 1996) or UV-induced stress (Conconi et al 1996b). On the other hand, the KODA level is transiently increased at the very early stage of flower budding in D. caryophyllus, E. russelianum and P. nil.…”
supporting
confidence: 64%
“…At present, it is unclear whether the lipid-bound OPDA/dn-OPDA in the membranes is synthesized in situ from MGDG or DGDG or alternatively, OPDA/dn-OPDA is synthesized from free 18:3/16:3 and then incorporated into glycerol (Schaller et al, 2004). The latter possibility is supported by substantial amount of free 18:3 and 18:2 that were detected in tomato leaves after wounding (Conconi et al, 1996). However, Buseman et al (2006) have shown that within the first 15 min after wounding, levels of OPDA-dnOPDA MGDG, OPDA-OPDA MGDG, and OPDA-OPDA DGDG increased 200 to 1000 folds.…”
Section: The Alternative Routes Of Ja Biosynthesismentioning
confidence: 99%
“…5) following elicitation with 50 µM MeJA. Support for the involvement of a lipolytic activity in the biosynthesis of jasmonates came from the observations of Mueller et al (1993) and Conconi et al (1996) that elicitation or wounding of plants caused rapid and transient changes in the lipid composition of plant cell membranes. Phospholipase A2 (PLA2, Conconi et al 1996) is located in the plasma membrane and can not directly attribute to JA biosynthesis which takes place at least in the first part in chloroplasts.…”
Section: Pharmacological Analysis Of Meja-induced Cell Deathmentioning
confidence: 99%